Diagnosis of Childhood Apraxia of Speech: A Systematic Review - Sayahi, Fatemeh; Jalaie, Shohreh (Journal of Diagnostics, 2016)
This review employed to establish frequency usage of clinical markers and diagnostic tests for childhood apraxia of speech. following databases were searched for published papers between 1980 and 2015 looking for clinical studies used the six introduced tests for motor speech performance; Web of Science, Scopus, CINAHL and Pubmed. . The review considered articles which for children at or below elementary school age with diagnosis of childhood apraxia of speech. Fifty seven articles met the inclusion criteria. Studies included other developmental motor speech disorders as well as childhood apraxia of speech were excluded. Twenty four articles excluded from the study and thirty three studies were reviewed. Twenty articles were in diagnostic tests and thirteen articles were in clinical markers. The Verbal Motor Production Assessment for Children is the most reliable diagnostic test for diagnosis of childhood apraxia of speech, and Inconsistency as well as vowel errors are the most frequent clinical markers.